Rate adaptive resource allocation in orthogonal frequency division multiple access system using multi-objective immune algorithm - Zheng-Yi, Chai; Si-Feng, Zhu; Lian-Feng, Shen (International journal of communication systems, 2014)
SUMMARY Rate adaptive downlink resource allocation in orthogonal frequency division multiple access system is a constraint optimization problem, which is to maximize the minimum data rate of the user subject to constraint that total power cannot exceed a given value. How to handle the constraint is a key issue for constrained optimization problem. Different with the available schemes on constraint handling, the proposed algorithm converts the constraint into an objective. Then, the resource allocation is combined into a multi‐objective optimization problem. An improved multi‐objective optimization algorithm based on artificial immune system is proposed to solve it. The simulation results show that, compared with previous schemes, the proposed algorithm performs remarkable improvement in sum capacity. Copyright © 2013 John Wiley & Sons, Ltd. Different with the available schemes on constraint handling, the proposed algorithm converts the constraint into an objective. Then, the resource allocation is combined into a multi‐objective optimization problem. An improved multi‐objective optimization algorithm based on artificial immune system is proposed to solve it.